Production Of Fructosyltransferase And Fructooligosaccharides By Penicillium Simplicissimum - Yazid, Noraziah Abu (2010)

(untitled)
Fructooligosaccharides (FOS) produced from natural resources as an alternative sweetener has received greater attention and sucrose is the common carbon source for its production. To minimize the production cost, feasibility of using low cost substrates derived from local agricultural resources such as sugarcane juice was chosen to replace the pure sucrose. Several fungi were screened for their ability to produce fructosyltransferase (FTase) and FOS. Penicillium simplicissimum was found to be a potent producer for FTase and FOS with the highest FTase activity at 5.54 X 102 IU/ml and FOS yield per sucrose consumed of 0.39 g/g, respectively.